A View of an Unusual Route for Certain Phosphorus Ylide - M. Al-Zaydi, Khadijah (Asian Journal of Chemistry, 2014)
An abnormal route for the synthesis of (5-(2-(2-cyanophenyl)hydrazono)-2,3-bis(methoxycarbonyl)-4-phenylcyclopent-2-enyl)triphenyl phosphonium (5) has been patented. The synthesis of compound (5) was performed by the reaction of 2-(2-(1,3-dioxo-1-phenylpropan-2-ylidene)hydrazinyl)benzonitrile with dimethylacetylene dicarboxylate in dichloromethane at room temperature for 2 h in order to yield a cyclic intermediate. The subsequent addition of triphenylphosphine afforded the desired product as interesting crystals suitable for X-ray crystallographic analysis. The synthesized compound was characterized based on (FT-IR, NMR, elemental analysis and single crystal X-ray diffraction studies). A possible mechanism for the synthesis was also reported.